Analisis Buku Ajar Beste Freunde Deutsch für Jugendliche A2.1 Berdasarkan Teori OTT - Sri Prameswari Indriwardhani; Rania Fadhila Amirah (Nexus Publishing, 2024)
A good textbook is very important in the German language learning process and must meet certain criteria. This study aims to describe the suitability of Beste Freunde für Jugendliche A2.1 textbook based on Ott's theory proposed by Christine Ott. This research uses qualitative descriptive method. The research data were obtained from Beste Freunde für Jugendliche A2.1 book which consists of Kursbuch and Arbeitsbuch with documentation technique. The result shows that the book Beste Freunde für Jugendliche A2.1 fulfills Ott's criteria. The criteria include Grammar, Vocabulary, Landeskunde & Interkulturalität, Text and Content, Lernenden-Orientierung, and Weitere Analysedimensionen. The results of the analysis show that this textbook generally fulfills the criteria set by Ott. The book successfully teaches various grammatical phenomena from different linguistic levels in a systematic and functional manner, introduces vocabulary relevant to teenagers' daily lives, and provides guidance in understanding intercultural and regional aspects of German. However, there are shortcomings in the lexis aspect, especially in terms of the relationship between German and other languages, such as the origin of words from other languages, which are not discussed and not categorized in terms of cultural history.